Whole-genome sequencing and SNP analysis of Thai Cannabis sativa cultivar ‘Hang Kra Rog Phu Phan’ (Cannabaceae) - THAVATCHAI KAMOLTHAM; NOPHADON LUANGPIROM; NAPAPORN KUAMSAB; TANAWAN KUMMALUE; TANAWAT CHAIPHONGPACHARA (Society for Indonesian Biodiversity, 2025)
Abstract. Kamoltham T, Luangpirom N, Kuamsab N, Kummalue T, Chaiphongpachara T. 2025. Whole-genome sequencing and SNP analysis of Thai Cannabis sativa cultivar ‘Hang Kra Rog Phu Phan’ (Cannabaceae). Biodiversitas 26: 4946-4953. Cannabis (Cannabis sativa) is a herbaceous plant valued for its medicinal and therapeutic uses. In Thailand, the indigenous cultivar ‘Hang Kra Rog Phu Phan’ has long been applied in traditional medicine and is recognized for its high Tetrahydrocannabinol (THC) content. This study provides the first genomic characterization of this traditional Thai cultivar using Whole-Genome Sequencing (WGS). Fresh leaf samples were collected from a licensed cultivation site, and paired-end libraries were prepared with the Illumina TruSeq DNA PCR-Free Kit. Sequencing on the NovaSeq 6000 platform produced 63.8 million raw reads (9.57 Gb), yielding 63.3 million high-quality reads (9.50 Gb) after trimming. Clean reads showed a 94.43% alignment rate to the ‘Pink Pepper’ reference genome, with an average depth of 11.39×. Variant calling identified 23.0 million genomic variants, including 18.5 million SNPs and 4.5 million Indels, with 6.04 million high-confidence SNPs retained after stringent filtering. Phylogenetic and principal component analyses revealed unexpected genomic proximity between ‘Hang Kra Rog Phu Phan’ and the CBD-dominant ‘CBD Shark’ cultivar, highlighting its distinct lineage among high-THC cultivars. These findings provide valuable genomic resources for precise cultivar authentication, marker-assisted breeding, conservation of native Thai germplasm, and functional genomics to advance cannabis-based therapeutics.